A survey on ambiguity awareness towards Malay system requirement specification (SRS) among industrial IT practitioners - Haron, Hazlina; Abd Ghani, Abdul Azim (Elsevier, 2015)
We conducted a survey amongst software development's IT practitioners on their awareness towards the ambiguity that occurs in the System Requirement Specification (SRS) written in the Malay language. Previous research shows that there exists an acknowledged and unacknowledged ambiguity when people deal with SRS. Our objective is to investigate and confirm that most likely IT practitioners in Malaysia tend to overlook the potential of ambiguities in the documentation of SRS written in the Malay language. Inaccurate SRS will usually give an impact towards an end product of software systems. We believe it can complicate software development processes and result in an unsatisfying agreement between user and software product team. The result shows that there exist ambiguity and vagueness in industrial Malay textual SRS in the form of multiple interpretations as users faced difficulties in understanding what the requirements of the SRS thereby significantly affecting the designing process.